A corpus study of the reversed causality - 이혜경 (언어연구, 2022)
This study analyzes the sentence-final causal connective -nikka in Korean. Based on corpus data, several meanings or functions of sentence-final -nikka clauses are identified, including epistemic causality, speech-act causality, and discourse marking, each with several subcategories. The findings corroborate earlier research that identified the first two meanings. The construction under discussion can serve as a discourse marker mainly modulating the impact of an assertion or speech act, since presenting a cause or reason for a situation is one of the most accessible means to express politeness. This study reports cases in which the conventional time sequence between a cause and a consequence is transposed while providing a cause for a speech act depicted in a main clause. Additionally, this study suggests that sentence-final -nikka clauses can stand alone without any deleted or preposed main clauses to impart circumstantial or additional information inferable from the context. To represent the various senses of the construction, a continuum model is proposed for both theoretical and practical reasons, wherein the core underlying meaning is argued to be causality, which is fleshed out in a specific context.
Keywords: cause; causality; sentence-final -nikka; continuum representation; stance marker; Korean